Of Benevolence and Unity: Unpacking China's Policy Discourses Toward Southeast Asia - Enrico Gloria (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2021)
While much attention has been directed on the security and economic implications of China’s rise in the region, research on the normative implications of China’s persistent attempt at projecting a positive major power identity continue to be lacking. This paper seeks to contribute to this growing literature, as it applies Social Identity Theory (SIT) in analyzing China’s discourses toward Southeast Asia from Mao to Xi. More specifically, it unpacks social identity phenomena within discourses reflected in official documents by using predicate analysis. Insights from the findings of this paper underscore China’s growing role as a normative power driven by a longstanding objective to be perceived positively and distinctively. Likewise, this paper also finds that there is a continuity with respect to China’s foreign policy discourse of depicting Sino-Southeast Asia relations as unique and united. There are also indications that Southeast Asia has consistently been presented as benefiting from its relations with China, thereby treating it as a prototype of what a Sino-centric order might offer for the rest of the world. Ultimately, China’s discourses of itself, Southeast Asia, and Sino-Southeast Asia relations point to major power aspirations of constructing a united in-group and a positive identity.